2011
DOI: 10.1016/j.ridd.2011.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Grammar predicts procedural learning and consolidation deficits in children with Specific Language Impairment

Abstract: The Procedural Deficit Hypothesis (PDH) posits that Specific Language Impairment (SLI) can be largely explained by abnormalities of brain structures that subserve procedural memory. The PDH predicts impairments of procedural memory itself, and that such impairments underlie the grammatical deficits observed in the disorder. Previous studies have indeed reported procedural learning impairments in SLI, and have found that these are associated with grammatical difficulties. The present study extends this research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
124
5
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 123 publications
(139 citation statements)
references
References 83 publications
(170 reference statements)
9
124
5
1
Order By: Relevance
“…They extend previous findings by showing, for the first time, that the sequence learning impairment in children with DD may be most pronounced in learning stages beyond a single practice session and the early, fast acquisition phase. Interestingly, a similar pattern of results has previously been reported for children with specific language impairment, a condition which often co-occurs with DD (Hedenius et al, 2011).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…They extend previous findings by showing, for the first time, that the sequence learning impairment in children with DD may be most pronounced in learning stages beyond a single practice session and the early, fast acquisition phase. Interestingly, a similar pattern of results has previously been reported for children with specific language impairment, a condition which often co-occurs with DD (Hedenius et al, 2011).…”
Section: Discussionsupporting
confidence: 84%
“…Subjects were asked to press one of four horizontally arranged buttons whenever the stimulus appeared in the corresponding location on the screen. Specifically, they were asked to ''catch the dog'' as quickly and accurately as possible by pressing the button corresponding to the circle in which the dog appeared (Hedenius et al, 2011). The sequence regularity was not mentioned.…”
Section: Stimuli and Proceduresmentioning
confidence: 99%
“…However, some studies report a deficit only in retention of learning, not in initial sequence learning [e.g., Desmottes, Maillart, & Meulemans, 2017; Hedenius et al, 2011]. Furthermore, a substantial number of other studies have also reported comparable learning in SLI on the SRT task [Gabriel et al, 2011; Gabriel, Meulemans, Parisse, & Maillart, 2015; Gabriel, Stefaniak, Maillart, Schmitz, & Meulemans, 2012; Lum & Bleses, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…Children with LD often have considerable difficulties during the literacy process, difficulties that become obstacles to the learning of reading and writing and to the association of the proposed contents [37,38,39]. The main feature of this kind of difficulty is the low efficiency and performance in activities such as reading, writing, and mathematics in relation to what could be expected from children according to their intelligence and opportunities [31].…”
Section: Discussionmentioning
confidence: 99%